2017
DOI: 10.1038/tp.2017.103
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent social-cognitive effects of intranasal oxytocin delivered with novel Breath Powered device in adults with autism spectrum disorder: a randomized placebo-controlled double-blind crossover trial

Abstract: The neuropeptide oxytocin has shown promise as a treatment for symptoms of autism spectrum disorders (ASD). However, clinical research progress has been hampered by a poor understanding of oxytocin’s dose–response and sub-optimal intranasal delivery methods. We examined two doses of oxytocin delivered using a novel Breath Powered intranasal delivery device designed to improve direct nose-to-brain activity in a double-blind, crossover, randomized, placebo-controlled trial. In a randomized sequence of single-dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(53 citation statements)
references
References 70 publications
5
48
0
Order By: Relevance
“…Another of our papers was also published recently, where we studied 16 autistic patients and delivered the same drug with our device [16]. Although this was a small crossover study with 16 patients, and we used only one single dose, we saw changes in some of the end points, which is very encouraging.…”
Section: How Does Optinose Delivery Technology Hope To Overcome the Dsupporting
confidence: 52%
“…Another of our papers was also published recently, where we studied 16 autistic patients and delivered the same drug with our device [16]. Although this was a small crossover study with 16 patients, and we used only one single dose, we saw changes in some of the end points, which is very encouraging.…”
Section: How Does Optinose Delivery Technology Hope To Overcome the Dsupporting
confidence: 52%
“…There is some human evidence that intranasal oxytocin administration increases central concentrations of oxytocin [39], however, it is unknown if this increase is due to direct nose-to-brain transport or through delivery across the blood brain barrier (BBB) via peripherally circulating blood. We have previously shown that an 8IU dose of oxytocin modulates social cognition [40] and amygdala activity, and that IV oxytocin administration (despite eliciting similar peripheral concentrations) does not elicit effects, which is consistent with nose-to-brain transport of oxytocin with intranasal administration [31,41]. However, the dose-and route-response effects on pupil activity, and its relationship with brain activity, are uncertain.…”
Section: Introductionmentioning
confidence: 57%
“…in response to reward [39]). Findings like these may question the sensitivity of methods that rely on much briefer stimulus exposures, such as visual probe paradigms [40][41][42] in detecting differences between groups that vary in empathic traits. There is widespread enthusiasm for the idea that electrophysiological methods with high temporal resolution may further clarify the temporal brain dynamics of empathy [43,44] and distinguish between competing explanatory models.…”
Section: Discussionmentioning
confidence: 99%